2002
DOI: 10.1590/s0074-02762002000800014
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian distribution of Amblyomma varium Koch, 1844 (Acari: Ixodidae), a common parasite of sloths (Mammalia: Xenarthra)

Abstract: Amblyomma varium, commonly known in Brazil as the "carrapato-gigante-da-preguiça" (sloth'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 9 publications
3
18
0
1
Order By: Relevance
“…In the present study, adults of A. geayi and adults and nymphs of A. varium were identified on B. tridactylus, corroborating the studies of SERRA-FREIRE et al (1993) andMARQUES et al (2002), who also identified adults of these same species of ticks in this same host in the North region of Brazil. Additionally, in the present study, ten nymphs of A. geayi were identified from B. tridactylus for the first time; nymphs of this species of tick had only been previously reported in the Brazilian Amazon region in Bradypus variegatus by MARTINS et al (2013) in the municipality of Belém, state of Pará.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, adults of A. geayi and adults and nymphs of A. varium were identified on B. tridactylus, corroborating the studies of SERRA-FREIRE et al (1993) andMARQUES et al (2002), who also identified adults of these same species of ticks in this same host in the North region of Brazil. Additionally, in the present study, ten nymphs of A. geayi were identified from B. tridactylus for the first time; nymphs of this species of tick had only been previously reported in the Brazilian Amazon region in Bradypus variegatus by MARTINS et al (2013) in the municipality of Belém, state of Pará.…”
Section: Resultssupporting
confidence: 92%
“…Ticks species Amblyomma geayi and Amblyomma varium are usually recorded parasitizing sloths (MARQUES et al, 2002;LABRUNA et al, 2009;SOUZA et al, 2016). In the present study, adults of A. geayi and adults and nymphs of A. varium were identified on B. tridactylus, corroborating the studies of SERRA-FREIRE et al (1993) andMARQUES et al (2002), who also identified adults of these same species of ticks in this same host in the North region of Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Neumann (1899) described A. varium (variety albida) from an allegedly Chilean specimen. However, Chile is outside the range of the hosts (sloths of the families Bradypodidae and Megalonchydae) of A. varium (Marques et al 2002). We consider this finding a result of mislabelling rather than an indication of the presence of A. varium in Chile.…”
Section: Resultsmentioning
confidence: 88%
“…Although most of the tick-host reports cited in this study have been reported in earlier studies conducted in Brazil and in Argentina (FONSECA, 1933;ARAGÃO, 1936;LABRUNA et al, 2005LABRUNA et al, , 2007LABRUNA et al, , 2009MARTINS, J., et al, 2006;MARTINS, T., et al, 2009MARTINS, T., et al, , 2013MARTINS, T., et al, , 2015 (MARQUES et al, 2002). The present record of nymphs of A. varium on B. variegatus in the FPZSP is consistent with an earlier study which found that nymphs of this tick species use sloths of the genus Bradypus as hosts.…”
Section: Introductionmentioning
confidence: 72%